The influence of dwelling design on the performance of indoor ventilation / Siti Suhaila Mohd Hashim - Mohd Hashim, Siti Suhaila (Faculty of Architecture, Planning and Surveying, 2015)
The factor of hot-humid climate in Malaysia makes the people mostly spent their time inside the building and 65% of their indoor time is in house. The comfortable environment inside dwelling is really needed to achieve comfort level for occupant. A building should be designed to fulfil the comfort level either by using natural ventilation, mechanical ventilation or both of it. This study is to investigate the correlation between building design and the performance of indoor ventilation to achieved good thermal comfort for dwelling in Malaysia. Natural ventilation in dwelling allows the fresh air that can increase the comfortable level. To provide adequate fresh air inside dwelling, types opening used at dwelling can be affected. To achieve the investigation, some equipment is used to easily get accurate data reading. The data reading must directly get from site observation towards chosen types of dwelling types. It was found that the uses of side hung window types can be better option for achieved natural ventilation inside dwelling. But in this modern living, people more preferred to use mechanical ventilation system such as fan or air-conditioning system to achieve comfort inside their dwelling. The factor of low air flow rate enter the house can contribute to increase of temperature level that can trap heat inside house. By this problem, occupants choose to use mechanical ventilation system for reducing temperature. Buildings should be designed to maximize the use of natural ventilation and minimise the use of mechanical ventilation, because the use of natural ventilation is better option to give fresh air inside the building.